Studi Komparatif Metode Demonstrasi dan Eksperimen terhadap Keterampilan Proses Sains Siswa Sekolah Dasar - Rajata, Reiki Bobby; Suryani, Ela (Universitas Muhammadiyah Magelang, 2026)
This study compares the impact of demonstration and experimental methods on the science process skills of elementary school students, covering abilities such as observing, classifying, and communicating. Using a sample of 74 students divided into two equal groups, data were collected through evaluation tests, questionnaires, and observations. Research instruments measured skills before and after the intervention, with data analyzed via statistical tests. Results from the independent t-test yielded a significance value (2-tailed) of 0.675 (p > 0.05), indicating no significant difference in science process skills between students taught using the demonstration method versus the experimental method. Despite the lack of statistical significance, the demonstration method produced slightly higher average scores, with a mean difference of 0.34. Both methods offer distinct advantages depending on student learning styles. In conclusion, while both approaches effectively support science process skills, the demonstration method showed a marginal superiority in this specific context.